Downov sindrom in telesna dejavnost - Jovičevič, Liza (Šport (Ljubljana), 2022)
The purpose of this article is to present guidelines for physical activity in children with Down syndrome. Today, we know that through physical activity, like all people, people with Down syndrome achieve a new quality of life. It is important not only to maintain their psychophysical abilities, but also to develop socialization and creative use of free time. Adults have an important role to play in children‘s development and learning, as this can alleviate individual problems and even eliminate some. Physical activity is very important as it reduces the chance of a child becoming overweight. It has a positive effect on well-being, relationships and self-confidence. This article presents Down syndrome and its cause, describes the physical and mental characteristics of people with Down syndrome, and diseases that are more common. In the following, we present guidelines for consideration in the composition of a physical activity program for children with Down syndrome.
Keywords: Downov sindrom; otroci; šport; telesna aktivnost